HASIL BELAJAR MATERI FPB DAN KPK MELALUI METODE PEMBELAJARAN KOOPERATIF STAD: HASIL BELAJAR MATERI FPB DAN KPK MELALUI METODE PEMBELAJARAN KOOPERATIF STAD - Nurdin Nurdin (Jurnal Tunas Pendidikan, 2021)
The implementation of mathematics learning in MIN 4 Bungo must be created actively, innovatively, creatively, effectively, and pleasantly through STAD's educational cooperative learning. This condition indicates that the STAD cooperative learning model has not been implemented or used optimally for mathematics learning on FPB and KPK material, including in MIN 4 Bungo. Therefore, Classroom Action Research was carried out in collaboration with teachers and principals. The goal is to describe the effectiveness of using STAD cooperative learning to improve the quality of learning. Classroom Action Research uses descriptive qualitative methods of cycle models: planning, implementing, observing, and reflecting. The subjects were students and teachers of class V MIN 4 Bungo Semester I in 2019. The results: (1) For mathematics learning in class V MIN 4 Bungo requires STAD cooperative learning model. (2) The application of STAD cooperative learning can improve understanding of the FPB and KPK concepts. (3) Improvements in mathematics learning in grade V MI can be carried out through CAR so that the learning process and the results are better quality. (4) The obstacle is limited time, materials / teaching aids, and the ability of teachers and students. Conclusion: The handling of problems faced by students of class V MIN 4 Bungo in improving understanding of the FPB and KPK concepts through STAD cooperative learning needs to be carried out in a planned, systematic and sustainable manner so that students gradually master the competencies related to mathematics learning.